Entre a caneta e o pandeiro: letras e enredos de agremiações afrodescendentes em Florianópolis – SC (1920 a 1950) - Rascke, Karla Leandro (2018)
This research such proposes to apprehend sociabilities and solidarities in associations organized by afrodescendants in Florianópolis/SC between 1920 and 1950. Based on sources such as newspapers, photographs, statutes and documents of associations formed by afrodescendants, we perceive a political reconfiguration of the city and new ways of experiencing the public space by african cultures. Different associations (clubs, blocks, cords, ranches and samba schools, cacumbi groups, religious brotherhoods, soccer clubs, black communities) mobilized efforts for the literacy of their members or impoverished popular groups, noting that in this period, in the space of political instances, many men and women of african origin. In this way, we seek to understand how these associations articulated solidarities and sociabilities of afrodescendant populations in the midst of the new political and cultural conjuncture of Florianopolis, based on the reformulation of political elites and the changes in the configuration of the Republic, especially with the New State